2018 year in review: Part 2 of 4: Neonatal lung disease. Issue 6 (26th February 2019) - Auten, Richard L.
Abstract: Pediatric Pulmonology publishes original research, reviews and case reports related to a wide range of children's respiratory disorders. This review (Part 2 of a 4‐part series) summarizes the past year's publications in the topic area of neonatal lung diseases, in the context of selected literature from other journals relevant to the discipline.